A Color of His Own - Lionni, Leo, 1910- (New York : Knopf, 2006)
A little chameleon is distressed that he doesn't have his own color like other animals.
Originally published: A colour of his own. London : Abelard-Schuman, 1975.
Keywords: Chameleons -- Fiction